ANALISIS FAKTOR YANG MEMPENGARUHI RETURN SAHAM PERUSAHAAN SEKTOR PERTANIAN PADA MASA PANDEMI COVID-19 - Widya Andreyna; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
To analyze the factors that influence stock returns of agricultural sector companies, this study was conducted. The population in this study are agricultural sector companies listed on the (Indonesian Stock Exchange) during the pandemic. Covid-19 was confirmed to have entered Indonesia. Sampling was selected directly from the IDX, namely as many as thirty agricultural sector companies listed on the IDX and have uploaded their annual reports as of December 30, 2020. The data analysis method used is multiple linear regression analysis, model feasibility Test (F test), partial Test (test t), Test of determination. The results of this study are the independent variables Solvency Ratio, Liquidity Ratio, Profitability Ratio effect simultaneously and partially on the dependent variable, namely stock returns.